Construire un problème : un premier pas vers l'investigation en sciences. Analyse d’une formation d’enseignants de primaire en contexte français et colombien - Luz Helena Martínez Barrera; Cécile de Hosson; Nicolas Décamp (Recherches en Éducation)
Science teaching has undergone significant transformations in terms of pedagogical orientation. These transformations reflect the evolution of an international framework highlighting more open procedures based on "inquiry". In this context, both French and Colombian science curricula require teachers to create problems leading to the implementation of inquiry-based science teaching sequences. Teachers must also motivate students to participate more actively in the process of the scientific knowledge construction. Consequently, helping teachers in the task of designing a problem appears as an essential step for inquiry-based science education to be implemented. In this research, we focus on what favors the construction of scientific problems. We designed an in-service training session for primary school teachers who have no prior specialization in scientific fields. This training session leans on the use of a scientific topic (the bouncing of the balls) that rarely appears in primary school science curricula. The training session is evaluated through the analysis of the teachers’ interactions whithin the "problematization" theoretical framework. This allows to understand which elements inhibit or favor the emergence of problems allowing (1) science inquiry (2) the construction of knowledge associated with the phenomenon of bouncing (influence of physical parameters, construction of characteristic scales, etc.).